Implementasi Fault Management (Manajemen Kesalahan) Pada Network Management System (NMS) Berbasis SNMP - Yuli Sholikatin; Nur Rohman Rosyid (Jurnal Teknik Informatika dan Sistem Informasi, 2017)
The use of computer network technology to meet the needs of information quickly and diverse, resulting in the increasingly widespread and increasing complexity of a computer network. Therefore, we need a supporting facility to be able to supervise the network element that is by using Network Management System (NMS). The NMS model established by ISO includes 5 conceptual areas, there are Fault, Configuration, Accounting, Performance and Security Management (FCAPS). One area that will be implemented in this research is Fault Management. The mechanism that will be used for error management is by detecting the occurrence of errors and sending notifications via email when the error appears, then logging report and make a diagnosis and to further recommend the solution to the error. The type of error reported in this system is errors when there is a failure of connectivity on the network device, errors due to services that are not running and not in accordance with the request, errors when high RAM usage, CPU load increases and the use of hard drives which started full. From the research results obtained, built NMS can send error notification and give solution recommendation via email to the network admin so if there is a network error, Fault Management activities can be done as early as possible so that the problem does not result in the deterioration of network quality.Â Kata kunci--Network Management; NMS; Fault Management; SNMP; System InformationÂ